Odpowiedź:
t)
[tex]x^{2} - (x - 3)(x - 1) = 1[/tex]
[tex]x^{2} - x^{2} + x + 3x - 3 =1[/tex]
[tex]4x = 4[/tex]
[tex]x = 1[/tex]
u)
[tex]2x^{2} - (2x + 1)(x - 2) = 5[/tex]
[tex]2x^{2} - 2x^{2} + 4x - x + 2 = 5[/tex]
[tex]3x = 3[/tex]
[tex]x = 1[/tex]
w)
[tex]x^{2} - 2 = (x + 2)(x + 4)[/tex]
[tex]x^{2} - 2 = x^{2} + 4x + 2x + 8[/tex]
[tex]- 10 = 6x[/tex]
[tex]x= -\frac{10}{6} = - \frac{5}{3}[/tex]
ż)
[tex](x - 3)(4x + 2) = 4x^{2} + 3[/tex]
[tex]4x^{2} + 2x -12x - 6 = 4x^{2} + 3[/tex]
[tex]- 10x = 9[/tex]
[tex]x = - \frac{9}{10}[/tex]